Pole piece and battery
By adding ion path enhancer to the electrode sheet, a gradient-distributed ion channel and electron channel is formed, which solves the problem of poor contact between the active substance and the electrolyte caused by thick electrodes, and improves the energy density and service life of the battery cell.
Patent Information
- Application Number
- CN202510008045.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
Thick electrodes lead to poor contact between the active substance and the electrolyte, longer migration path of lithium ions, increased concentration difference polarization, decreased energy density of the battery cell and shortened life.
The ion path enhancer is added to the electrode sheet to form gradient distributed ion channels and electron channels, improve the transfer efficiency of lithium ions, balance electron and ion transfer, and reduce battery polarization.
By increasing the ion channel, the transfer time of lithium ions is reduced, the energy density and service life of the battery are improved, and the storage and cycling performance of the battery is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a pole piece and a battery. Background Art
[0002] As a highly efficient energy storage device, lithium-ion batteries are widely used in various fields such as digital, power tools, electric vehicles and energy storage due to their high energy density, long cycle life, low maintenance cost and no memory effect. With the continuous development of electric vehicles and smart terminal technologies, the market has put forward new requirements for the endurance of lithium-ion batteries.
[0003] Thick electrodes can effectively reduce battery volume and increase energy density, but the active materials at the bottom of the thick electrodes cannot contact the electrolyte well, the lithium ion migration path becomes longer, the concentration polarization increases, and the charge transfer dynamics deteriorate, ultimately leading to a decrease in the energy density of the battery cell and a shortened battery life. Summary of the invention
[0004] In order to solve or partially solve the problems existing in the related art, the present application provides a pole piece and a battery, which can increase the ion channel by adding an ion channel enhancer to the pole piece to reduce the transfer time of lithium ions, thereby improving the energy density and service life of the battery cell.
[0005] The first aspect of the present application provides a pole piece, comprising a current collector; at least two coating layers, the coating layers are sequentially stacked on the current collector, the coating layers contain an ion channel enhancer and a conductive agent; in a direction away from the current collector, the content percentage of the ion channel enhancer in the coating layers gradually decreases.
[0006] In combination with the first aspect, in a possible implementation of the first aspect, the innermost coating layer close to the current collector is used as the innermost coating layer, the ion channel enhancer in the innermost coating layer accounts for 60-90% of the total mass of the ion channel enhancers in all the coating layers, and the conductive agent in the innermost coating layer accounts for 5-35% of the total mass of the conductive agent in all the coating layers.
[0007] In combination with the first aspect, in a possible implementation of the first aspect, the coating layer is stacked in sequence with n layers in a direction away from the current collector, wherein n≥2; and the ratio of the content of the conductive agent in the nth coating layer to the content of the conductive agent in the n-1th coating layer is (1.2-4):1.
[0008] In combination with the first aspect, in a possible implementation of the first aspect, the ratio of the content of the ion channel enhancer in the nth coating layer to the content of the ion channel enhancer in the n-1th coating layer is (0.1-0.8):1.
[0009] In combination with the first aspect, in a possible implementation of the first aspect, the coating layer further includes a conductive agent and a binder; the binder is selected from a combination of one or more of polyvinylidene fluoride, hydroxymethyl cellulose, PAA and SBR. The conductive agent is selected from a combination of one or more of carbon black, Ketjen black, acetylene black, carbon nanotubes, carbon fibers and graphene.
[0010] In combination with the first aspect, in a possible implementation of the first aspect, an active material is also included, and the mass ratio of the active material, the conductive agent, the binder and the ion path enhancer in the coating layer is: (90-98): (0.5-6): (0-5): (0.5-8).
[0011] In combination with the first aspect, in a possible implementation of the first aspect, the ion channel enhancer is selected from a combination of one or more of hectorite or lithiated aluminum silicalite.
[0012] In combination with the first aspect, in a possible implementation of the first aspect, the average compaction density of the pole piece is 1.2-2.0 g / cm 3 The average surface density of the pole piece is 200-800g / m 2 .
[0013] In combination with the first aspect, in a possible implementation manner of the first aspect, the pore diameter of the ion channel enhancer is 0.1 nm to 20 nm.
[0014] A second aspect of the present application provides a battery, comprising a positive electrode sheet, a separator and a negative electrode sheet stacked on each other, wherein at least one of the positive electrode sheet and the negative electrode sheet has the structure of the electrode sheet as described in any of the above items.
[0015] The technical solution provided by this application may have the following beneficial effects:
[0016] The pole piece and battery of the present application include a current collector; at least two coating layers, which are sequentially stacked on the current collector, and the coating layers contain an ion channel enhancer and a conductive agent; in the direction away from the current collector, the content percentage of the ion channel enhancer in the coating layer gradually decreases, and the ion channel enhancer can be added to the pole piece, and the ion channel enhancer can be combined with the conductive agent to form a gradient distribution, so that an efficient ion channel and an electron channel can be constructed at the same time, thereby realizing dual rapid transfer of electrons and lithium ions, reducing the polarization of the battery by balancing the transfer of electrons and ions, and improving the energy density and service life of the battery cell.
[0017] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION
[0018] The embodiments of the present application will be described in more detail below. Although the embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0019] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "a", "an" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used in this article refers to and includes any or all possible combinations of one or more associated listed items.
[0020] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0021] In the related technologies, lithium-ion batteries, as a highly efficient energy storage device, are widely used in various fields such as digital, power tools, electric vehicles and energy storage due to their advantages such as high energy density, long cycle life, low maintenance cost and no memory effect. With the continuous development of electric vehicles and smart terminal technologies, the market has put forward new requirements for the endurance of lithium-ion batteries, and it is urgent to develop a lithium-ion battery with higher energy density.
[0022] The energy density of lithium-ion batteries is not only related to electrode materials, but also closely related to factors such as electrode structure, preparation process, and auxiliary materials. Using fewer resources and lower costs to produce batteries with better performance is the pursuit of all battery manufacturers. Among them, the development of thick electrodes can reduce the use of current collectors, while increasing the active material loading per unit area, which helps to reduce costs and increase efficiency. However, thick electrodes also bring certain problems. The active materials at the bottom layer are not easy to contact with the electrolyte, the lithium ion migration path becomes longer, the concentration polarization increases, and the charge transfer dynamics become worse, which ultimately leads to the battery cell capacity not meeting expectations, accompanied by problems such as easy lithium precipitation at low temperatures and deterioration of charging capacity. At present, these problems are mainly improved by using a multi-layer coating method to adjust the pore structure of the pole piece and the electrolyte's liquid retention capacity. Therefore, a new way is needed to expand the ion channel to increase the transmission efficiency of the active materials at the bottom layer of the electrode.
[0023] In response to the above problems, the embodiments of the present application provide a pole piece and a battery, which can simultaneously construct an efficient ion path and an electron path by adding an ion path enhancer to the pole piece. The ion path enhancer cooperates with a conductive agent to form a gradient distribution, thereby achieving dual rapid transfer of electrons and lithium ions, reducing the polarization of the battery by balancing the transfer of electrons and ions, and improving the energy density and service life of the battery cell.
[0024] The technical solutions of the embodiments of the present application are described in detail below.
[0025] The present application provides a pole piece, comprising: a current collector; at least two coating layers, the coating layers are sequentially stacked on the current collector, the coating layers contain an ion channel enhancer and a conductive agent; in a direction away from the current collector, the content percentage of the ion channel enhancer in the coating layer gradually decreases.
[0026] In some embodiments, multiple coating layers may be stacked on the current collector, such as 2 layers, 3 layers, etc. The thickness of each coating layer may be substantially the same or different, and the surface density of each coating layer may be 50-200 g / m 2 , the coating layer contains an ion channel enhancer and a conductive agent.
[0027] In the present application, by adding ion path enhancers and conductive agents to the coating layer, the ionic conductivity on the collector side and the electronic conductivity away from the collector side can be enhanced, balancing the two, while optimizing the electron and ion transmission channels in the entire electrode to achieve dual rapid transfer of electrons and lithium ions, so as to achieve the purpose of reducing battery polarization and thereby increase the capacity of the battery cell.
[0028] In some possible embodiments, the ion channel enhancer is selected from a combination of one or more of laponite or lithiated aluminum silicalite. The ion channel enhancer can form multiple ion channels in the coating layer, which is beneficial to improving the transfer efficiency of lithium ions.
[0029] In some possible embodiments, the average compaction density of the pole piece is 1.2-2.0 g / cm 3 , average surface density is 200-800g / m 2 The surface density of each coating layer is 50-200g / m 2 .
[0030] In some possible embodiments, the coating layer further includes a conductive agent and a binder; the binder is selected from a combination of one or more of polyvinylidene fluoride, hydroxymethyl cellulose, PAA and SBR. The conductive agent is selected from a combination of one or more of carbon black, Ketjen black, acetylene black, carbon nanotubes, carbon fibers and graphene, which is not limited in this application.
[0031] In some possible embodiments, active materials are also included, and the mass ratio of the active materials, conductive agents, binders and ion channel enhancers in the coating layer is: (90-98): (0.5-6): (0-5): (0.5-8). Preferably, the mass ratio of the active materials, conductive agents, binders and ion channel enhancers in the coating layer is: (92-96): (1-5): (0-3): (0.5-5). The coating layer contains the above-mentioned components, which can better improve the transfer efficiency of lithium ions.
[0032] In some possible embodiments, the innermost coating layer close to the current collector is used as the innermost coating layer, the ion channel enhancer in the innermost coating layer accounts for 60-90% of the total mass of the ion channel enhancers in all coating layers, and the conductive agent in the innermost coating layer accounts for 5-35% of the total mass of the conductive agent in all coating layers. The mass percentages of the ion channel enhancer and the conductive agent in the coating layer meet the above ratios, which can better balance the electron and ion conduction and reduce battery polarization.
[0033] In some possible embodiments, the coating layers are stacked in sequence with n layers in a direction away from the current collector, wherein n≥2; the ratio of the content of the conductive agent in the nth coating layer to the content of the conductive agent in the n-1th coating layer is (1.2-4):1, and in the multi-layer coating layers, the amount of conductive agent added in the coating layer away from the current collector gradually increases.
[0034] In some possible embodiments, the ratio of the content of the ion channel enhancer in the nth coating layer to the content of the ion channel enhancer in the n-1th coating layer is (0.1-0.8):1. In the multi-layer coating layer, the amount of the ion channel enhancer added in the coating layer away from the current collector gradually decreases.
[0035] In some possible embodiments, the pore size of the ion channel enhancer is 0.1nm to 20nm. When the ion channel enhancer is hectorite, the average particle size of the ion channel enhancer is between 20-50nm, the sheet thickness is between 1-15nm, and the hectorite is very easy to form a stable colloid in an aqueous solution, which can be used as a binder, and the use of the binder can be reduced or eliminated; when the ion channel enhancer is lithiated aluminum silicate, the average pore size of the ion channel enhancer is 0.1nm to 20nm, and the average particle size is 10nm to 2000nm.
[0036] An embodiment of the present application also provides a method for preparing the above-mentioned pole piece, the preparation method comprising: coating at least two slurries on the surface of a current collector, drying and rolling the current collector coated with at least two slurries to form a coating layer of the slurry on the current collector, and preparing the pole piece.
[0037] The electrode coated with the coating layer prepared by the preparation method, the ion channel enhancer in the coating layer can increase the ion channel, improve the transmission efficiency of lithium ions, improve the storage and cycle performance of the battery, and thus enhance the comprehensive performance of the lithium-ion battery.
[0038] An embodiment of the present application also provides a battery, comprising a positive electrode sheet, a separator and a negative electrode sheet stacked on each other, wherein at least one of the positive electrode sheet and the negative electrode sheet has the structure of the above-mentioned electrode sheet, and during the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet, and the separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation; the electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0039] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on the surface of the positive electrode current collector. The positive electrode current collector may be a conventional metal foil or a composite current collector, such as aluminum foil. The positive electrode material layer may include a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent.
[0040] The specific types of the positive electrode current collector, positive electrode active material, positive electrode binder and positive electrode conductive agent of the present application are not limited, and any material known in the art for positive electrode materials can be used without limitation.
[0041] In some specific embodiments, as an example, the current collector can be selected from a metal foil or a composite current collector, for example, it can be selected from a copper foil; the negative electrode active material can be selected from graphite and / or silicon, such as natural graphite, artificial graphite, mesophase microcarbon beads (referred to as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy; the negative electrode binder can be selected from at least one of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluorovinylidene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB); the negative electrode conductive agent can be selected from at least one of carbon black, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon fibers, and superconducting carbon.
[0042] In some embodiments, the diaphragm of the present application can be arbitrarily selected from known porous structure diaphragms with good chemical stability and mechanical stability. The material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without special restrictions. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions.
[0043] In some embodiments, the negative electrode sheet, the separator, and the positive electrode sheet may be formed into an electrode assembly by a lamination process.
[0044] The battery disclosed in the embodiments of the present application can be used in electrical devices that use the battery as a power source or various energy storage systems that use the battery as an energy storage element. Electrical devices include but are not limited to mobile phones, tablets, computers, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc., which are not limited here.
[0045] The present application adds an ion channel enhancer to the coating layer on the current collector. The ion channel enhancer cooperates with the conductive agent to form a gradient distribution, thereby constructing an efficient ion channel and an electron channel at the same time, realizing dual rapid transfer of electrons and lithium ions, reducing the polarization of the battery by balancing the transfer of electrons and ions, improving the storage and cycle performance of the battery, and thus improving the overall performance of the lithium-ion battery.
[0046] In order to make the present invention easier to understand, the present invention will be further described in detail below in conjunction with examples, which are merely illustrative and are not intended to limit the scope of application of the present invention. The raw materials or components used in the present invention can be obtained by commercial routes or conventional methods unless otherwise specified.
[0047] Embodiment 1:
[0048] (1) Preparation of positive electrode sheet:
[0049] Lithium iron phosphate, conductive agent carbon nanotubes, and binder polyvinylidene fluoride were added to nitrogen methyl pyrrolidone (NMP) in a mass ratio of 100:3:2, and stirred under the action of a vacuum mixer until the system became a uniform positive electrode slurry. The positive electrode slurry was then evenly coated on the positive electrode current collector aluminum foil. After drying, cold pressing, cutting and slitting, a positive electrode sheet was obtained, wherein the positive electrode sheet surface density was 540g / m 2 , compacted density is 2.65g / m 3 .
[0050] (2) Preparation of negative electrode sheet:
[0051] First slurry: artificial graphite as the negative electrode active material, carbon black as the conductive agent, styrene-butadiene rubber as the binder, and laponite as the ion path enhancer are fully stirred and mixed in a proper amount of deionized water solvent in a mass ratio of 94.4%:2.0%:0.4%:3.2% to form a uniform first slurry.
[0052] Second slurry: artificial graphite as the negative electrode active material, carbon black as the conductive agent, styrene-butadiene rubber as the binder, and laponite as the ion path enhancer are fully stirred and mixed in a proper amount of deionized water solvent in a mass ratio of 93.6%:4.0%:1.6%:0.8% to form a uniform second slurry.
[0053] The first slurry and the second slurry are simultaneously coated on the surface of the negative electrode current collector copper foil through a multi-layer coating die head, the first slurry is coated on the surface of the current collector, and the second slurry is located on the surface of the first slurry away from the current collector. The coating amount ratio of the first slurry to the second slurry is 1:1; after drying, cold pressing, cutting, and slitting, a negative electrode sheet is obtained, wherein the average surface density of the negative electrode sheet is 260g / m 2 , compacted density is 1.6g / m 3 .
[0054] (3) Preparation of batteries:
[0055] PE porous polymer film is used as the separator.
[0056] The positive electrode sheet, the separator and the negative electrode sheet prepared as above are stacked in order, so that the separator is located between the positive and negative electrodes to play an isolating role, and then the battery cell is made into a battery cell by stacking the sheets. The battery cell is placed in an aluminum-plastic film bag that has been punched and formed. After baking and removing water, a carbonate-based electrolyte is injected (the solute is 1 mol / L LiPF6, and the volume ratio of the solvent EC (ethylene carbonate): DMC (dimethyl carbonate): DEC (diethyl carbonate) is 1:1:1). After vacuum packaging, the battery preparation is completed.
[0057] Embodiment 2:
[0058] The present embodiment provides a positive electrode sheet, a negative electrode sheet and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode sheet, the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the ion channel enhancer lithium laponite in the first slurry is 95.6%:1.5%:0.4%:2.4%, and the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the ion channel enhancer lithium laponite in the second slurry is 92.4%:4.4%:1.6%:1.6%.
[0059] Embodiment 3:
[0060] The present embodiment provides a positive electrode sheet, a negative electrode sheet and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode sheet, the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the ion channel enhancer lithium laponite in the first slurry is 94.6%:2.2%:0.4%:2.8%, and the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the ion channel enhancer lithium laponite in the second slurry is 93.1%:4.3%:1.9%:0.7%, and the coating amount ratio of the first slurry to the second slurry is 1.6:1.
[0061] Embodiment 4:
[0062] This embodiment provides a positive electrode sheet, a negative electrode sheet and a battery, and the preparation method thereof is basically the same as that of Embodiment 1, except that in the preparation of the negative electrode sheet, the ion channel enhancer used in the preparation of the first slurry and the second slurry is lithiated aluminum silicate.
[0063] Embodiment 5:
[0064] The present embodiment provides a positive electrode sheet, a negative electrode sheet and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode sheet, the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the ion channel enhancer lithium laponite in the first slurry is 97.4%:0.1%:0.4%:2.1%, and the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the ion channel enhancer lithium laponite in the second slurry is 90.8%:5.7%:1.5%:1.9%.
[0065] Embodiment 6:
[0066] The present embodiment provides a positive electrode sheet, a negative electrode sheet and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode sheet, the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the ion channel enhancer lithium laponite in the first slurry is 93.4%:2.4%:0.4%:3.8%, and the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the ion channel enhancer lithium laponite in the second slurry is 94.6%:3.6%:1.6%:0.2%.
[0067] Comparative Example 1:
[0068] The present embodiment provides a positive electrode sheet, a negative electrode sheet and a battery, and the preparation method thereof is basically the same as that of Embodiment 1, except that, in the preparation of the negative electrode sheet, only a first slurry is prepared, and the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber, and the ion path enhancer lithium laponite in the first slurry is 94%:3%:1%:2%, and the first slurry is coated on the surface of the current collector.
[0069] Comparative Example 2:
[0070] The present embodiment provides a positive electrode sheet, a negative electrode sheet and a battery, and the preparation method thereof is basically the same as that of Embodiment 1, except that, in the preparation of the negative electrode sheet, only a first slurry is prepared, and the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber, and the thickener carboxymethyl cellulose in the first slurry is 94%:3%:1%:2%, and the first slurry is coated on the surface of the current collector.
[0071] Comparative Example 3:
[0072] The present embodiment provides a positive electrode sheet, a negative electrode sheet and a battery, and the preparation method thereof is basically the same as that of Embodiment 1, except that, in the preparation of the negative electrode sheet, the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the thickener carboxymethyl cellulose in the first slurry is 94.9%:2.0%:1.0%:2.0%, and the mass ratio of the negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber, and the thickener carboxymethyl cellulose in the second slurry is 93.1%:4.0%:1.0%:2.0%.
[0073] The batteries of Examples 1-6 and Comparative Examples 1-3 were tested. First, the cells were formed. The formation steps were: 1. 0.05C charging for 2 hours; 2. Standing for 10 minutes; 3. 0.2C constant current and constant voltage charging to 3.8V, 0.05C cut-off; 4. Standing for 10 minutes; 5. 0.33C discharge to 2V.
[0074] Capacity test: Charge to 3.8V at 0.33C constant current and constant voltage, cut off at 0.05C, discharge to 2V at 0.33C constant current, and leave for 10 minutes between charge and discharge. Cycle three times, and use the third discharge capacity as the cell capacity. Cell energy density = capacity * 3.2.
[0075] DCIR test: 1. Discharge the battery at 0.33C to 1 / 2 of the divided capacity; 2. Leave it for 30 minutes; 3. Discharge the battery at a constant current of 1.5 times the divided capacity for 30 seconds and calculate the DCIR value.
[0076] Table 1 provides the battery test results of Examples 1-6 and Comparative Examples 1-3, with the DCIR and energy density of Comparative Example 2 used to measure other values.
[0077] Table 1
[0078]
[0079] 1) It can be seen from Examples 1-6 and Comparative Example 1 that Examples 1-6 set two coating layers on the negative electrode current collector, and the average value of the ion channel enhancer hectorite added in the negative electrode is 2%, and Comparative Example 1 sets a single coating layer on the current collector, and the content of the ion channel enhancer hectorite in the single coating layer is 2%, and the content of the ion channel enhancer added in the coating layers of Examples 1-6 and Comparative Example 1 is the same. The experimental results in Table 1 show that the battery internal resistance corresponding to Examples 1-6 is small and the energy density is large; the battery internal resistance corresponding to Comparative Example 1 is large and the energy density is small, that is, compared with Comparative Example 1, Examples 1-6 set two coating layers on the current collector to form a gradient distribution of conductive agent and ion channel enhancer, which can make the battery internal resistance smaller and the energy density higher.
[0080] 2) It can be seen from Comparative Example 1 and Comparative Example 2 that in Comparative Example 1, an ion channel enhancer is added to the coating layer, while in Comparative Example 2, no ion channel enhancer is added to the coating layer; the experimental results in Table 1 show that the battery corresponding to Comparative Example 1 has a smaller internal resistance and a larger energy density; the battery corresponding to Comparative Example 2 has a larger internal resistance and a smaller energy density, that is, compared with Comparative Example 2, Comparative Example 1 adds an ion channel enhancer in the coating layer, and the battery prepared by the same has a smaller internal resistance and a higher energy density.
[0081] 3) It can be seen from Examples 1-6 and Comparative Example 3 that Examples 1-6 set two coating layers on the current collector, and each coating layer is added with a gradient-distributed conductive agent and an ion channel enhancer, while Comparative Example 3 sets two coating layers on the current collector, but each coating layer is only provided with a gradient-distributed conductive agent. The experimental results in Table 1 show that the battery internal resistance corresponding to Examples 1-6 is smaller and the energy density is larger; the battery internal resistance corresponding to Comparative Example 3 is larger and the energy density is smaller, that is, compared with Comparative Example 3, Examples 1-6 add a gradient-distributed ion channel enhancer in the coating layer, and the battery produced by the battery has a smaller internal resistance and a higher energy density.
[0082] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A pole piece, characterized in that: include: current collector; At least two coating layers, the coating layers are sequentially stacked on the current collector, and the coating layers contain an ion channel enhancer and a conductive agent; The content percentage of the ion channel enhancer in the coating layer gradually decreases in a direction away from the current collector.
2. The pole piece according to claim 1, characterized in that: include: The innermost coating layer close to the current collector is used as the innermost coating layer, the ion channel enhancer in the innermost coating layer accounts for 60-90% of the total mass of the ion channel enhancers in all the coating layers, and the conductive agent in the innermost coating layer accounts for 5-35% of the total mass of the conductive agent in all the coating layers.
3. The pole piece according to claim 1, characterized in that: The coating layer is sequentially stacked with n layers in a direction away from the current collector, wherein n≥2; The ratio of the content of the conductive agent in the nth coating layer to the content of the conductive agent in the n-1th coating layer is (1.2-4):
1.
4. The pole piece according to claim 3, characterized in that: The ratio of the content of the ion channel enhancer in the nth coating layer to the content of the ion channel enhancer in the n-1th coating layer is (0.1-0.8):
1.
5. The pole piece according to claim 1, characterized in that: The coating layer also includes a conductive agent and a binder; The binder is selected from a combination of one or more of polyvinylidene fluoride, hydroxymethyl cellulose, PAA and SBR; The conductive agent is selected from one or more combinations of carbon black, Ketjen black, acetylene black, carbon nanotubes, carbon fibers and graphene.
6. The pole piece according to claim 5, characterized in that: The coating layer further comprises an active material, wherein the mass ratio of the active material, the conductive agent, the binder and the ion path enhancer in the coating layer is (90-98): (0.5-6): (0-5): (0.5-8).
7. The pole piece according to claim 1, characterized in that: The average compaction density of the pole piece is 1.2-2.0 g / cm 3 The average surface density of the pole piece is 200-800g / m 2 .
8. The pole piece according to claim 1, characterized in that: The ion channel enhancer is selected from laponite or lithiated aluminum silicate zeolite or a combination of one or more thereof.
9. The pole piece according to claim 1, characterized in that: The pore diameter of the ion channel enhancer is 0.1 nm to 20 nm.
10. A battery, characterized in that: The invention comprises a positive electrode sheet, a separator and a negative electrode sheet stacked on each other, wherein at least one of the positive electrode sheet and the negative electrode sheet has the structure of the electrode sheet according to any one of claims 1 to 9.
Citation Information
Patent Citations
Polymer lithium ion battery and manufacturing method of positive plate of battery
CN102779977A
Negative pole piece and lithium-ion battery
CN105742613A
Preparation method of multi-layer composite electrode and lithium ion battery of multi-layer composite electrode
CN115020642A
Composite electrode material and preparation method and application thereof
CN116646494A
Positive electrode active material and preparation method thereof, positive electrode plate and lithium battery
CN117334831A